Measuring the coupling coordination of land use functions and influencing factors: a case study in Beijing - Wang, Wenhui; Zhang, Jian (Frontiers in Ecology and Evolution, 2023)
Land use patterns significantly impact urban development by exerting production-living-ecological functions (PLEFs). Scientifically measuring the relationships among PLEFs is essential to support regional high-quality and sustainable development. However, the current identification methods of PLEFs are biased, and researches on the spatial distribution of coordination and conflict and their influencing factors in metropolitan are insufficient. This study proposed an improved PLEFs identification method to analyze the PLEFs in Beijing from 2000 to 2020 at a grid scale. Then, the coupling coordination degree (CCD) of PLEFS was estimated by employing spatiotemporal data and spatial statistical models. Finally, the impacts of the socioeconomic and natural factors on the CCD were quantified by the geographically weighted regression model (GWR). The results showed that from 2000 to 2020, (1) the areas with high CCD gathered in the plain areas with high PF and LF, and the low CCD areas clustered in the mountainous areas with low PF and LF; (2) the EF presented a closer positive relationship with CCD in the plain areas, while the positive impact of PF and LF on CCD was more substantial than EF in the mountainous areas; and (3) the population and GDP factors had high positive effects on CCD in the north and west mountain areas, and the altitude and slope factors negatively affected CCD in most areas of Beijing, except for a few areas in the southeast. Therefore, formulating a regional differentiation strategy to achieve the sustainable development of PLEFs in Beijing was crucial.